Reduction for Ordinary and Partial Differential Equations by Using Lie Group (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
In this publication, We have done Lie group theory is applied to reduce the order of ordinary differential equations (ODEs) with 1-parameter  and reduce a PDEs to ODEs . Also, set up algorithm to solve ODEs and PDEs to obtain the exact solution.